Description of the circulatory dynamics in the heart and lungs of inhabitants of sea level and high altitude through the dye dilution technique - Monge C., Carlos (1956)
The dilution technique has been used for the description of the circulatory dynamics in the heart and lungs of inhabitants of sea level and high altitude. The main purpose of this study was to measure the amount of blood in the lungs of these groups of people, through the formula of Newman, to show whether the natives of high altitudes have a greater amount of blood in the lungs. The following calculations were made: circulation time, volume, heart squeezing, intralorácico blood volume (Hamilton), central volume (Newman) and total blood volume. At sea level, 20 men and 15 women were studied. In altra (4,540 mts.) 10 men who were born and still living at 4,540 m were studied. When values are corrected per square meter of body surface, no marked difference between men and women at sea level, apart from the known hematologic differences. Natives live show longer circulation times, a volume slightly higher expulsion, increased blood volume and increased amount of blood in the lungs. When pulmonary blood volume, calculated with the formula of Newman, is expressed as a percentage of total blood volume, the high group also shows that individuals higher numbers of sea level.